Peran Guru Pendidikan Agama Islam terhadap Pengamalan Ibadah Shalat Wajib Peserta Didik di SDN 02 Maek Kabupaten Lima Puluh Kota - Silma Natalia; Alimir Alimir; Ulva Rahmi; Deswalantri Deswalantri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The aim of this research is to find out how Islamic Religious Education teachers at SDN 02 Maek, Limapuluh Kota Regency contribute to the implementation of mandatory student prayers. Data was collected for this research using qualitative descriptive methodology through observation, interviews and documentation. Even though elementary school learning hours are limited to performing midday prayers in congregation at PAI schools, teachers still carry out their role in helping students perform obligatory prayers, according to research findings. This is what happened to the Islamic Religious Education Teacher at SDN 02 Maek. At SDN 01 Maek, PAI professors participate in student prayer in several ways, including: The instructor provides information about prayer and applies it to students' actual situations. Islamic Religious Education Teachers convey information by connecting what they have learned so far with what students already know. Religious Education in Islam Teachers inspire students to participate in obligatory prayers by providing examples and inspiration regarding the importance of doing so. Religious Education in Islam By requiring children to pray every day at every school level, teachers provide direction and guidance. Religious Education in Islam Teachers educate by encouraging students to understand the meaning of each movement in prayer. Teaching the Islamic faith Instructors work with parents of students. Religious Education in Islam Instructors assess their students' ability to perform the required prayers.